Partisan Selective Exposure to Fake News Content - Ardi, Rahkman (UI Scholars Hub, 2019)
Selective exposure to political news in social media in Indonesia is escalating along with the increasing polarization of Indonesian people. This research aims to investigate: 1) differences in selective exposure to fake news content among incumbent and opposition supporters; 2) the association between critical thinking ability and partisans’ selective exposure. Repeated measures design was employed as the experiment design. Respondents were student activists of extra-campus organizations with particular political ideologies, who have pro-incumbent or pro-opposition preference. Seventy-one respondents were recruited, consisting of 34 incumbent (Jokowi) supporters and 37 opposition (Prabowo) supporters. Data was analyzed using independent t-test, a paired sample t-test, and correlational analysis. Results show that the opposition side was more inclined to demonstrate selective exposure by believing in fake news about their political enemy, compared to the incumbent supporters. This is shown by their tendency to believe and spread discrediting news about their political opponents rather than doing so for news which discredits their side. No association between critical thinking and partisan selective exposure was found. The implication of these results is that the critical point in debiasing is not necessarily predicated merely on analytical thinking ability but might also rest on one’s ability to think open-mindedly.